Cyclic Separating Reactors. - Aida, Takashi (John Wiley & Sons, 2007)
Cyclic Separating Reactors is a critical examination of the literature covering periodically operated separating reactors incorporating an adsorbent as well as a catalyst, aiming to establish the magnitude of performance improvement available with this type of reactor compared to systems in which the reactor and separator are separate units. The adequacy of present models is considered by comparison of simulation and experimental studies, and gaps in understanding or experimental verification of model predictions are identified. Separating reactors, including chromatographic reactors and press.